O papel da crença no mundo justo, da vitimização secundária e do sexismo societal no apoio à violência contra a mulher nas relações de namoro - Tavares, Suiane Magalhães (2021)
Dating violence against women is defined as a threat or actual use of physical, psychological, verbal / sexual, patrimonial and moral abuse. The way in which we see these situations can impact the lives of the people involved and interpersonal relationships. The Belief in a just word theory and its correlates: secondary victimization has a role in understanding this complex phenomenon. However, no research, as far as we know, has investigated the effect of BJW, secondary victimization and societal sexism in supporting violence against women in dating relationships. We raised the hypothesis that the phenomenon of secondary victimization mediates the relationship between societal sexism and support for violence and, in a second moment, we hypothesized the BJW as moderator of this relationship, and we went a little further, in a third moment, when manipulating the threat of BJW from observers in a heterogeneous sample. In Study 1 (N = 200), we manipulated societal sexism (individual vs. society) and found that people with high levels of sexism secondarily victimized a victim of violence. In Study 2 (N = 204), in addition to the manipulation of societal sexism, we included the manipulation of BJW. We verified the impact of secondary victimization in supporting violence once again, the BJW hypothesis was against the expected results. Finally, to help understand the previous process, we carried out Study 3 (N = 305), manipulating a situation that challenges the BJW, compared to a control situation. The results of this study showed a mediation of secondary victimization, as well as the stronger effect of moderating the victim's avoidance in the threat of BJW. In general, what we found confirms the results of previous findings, as well as extending the contribution to psychological research on the phenomenon in question, especially in the context of gender violence in the approach of the fair belief in a just world theory. In addition to highlighting the role of secondary victimization in legitimizing violence in women who are in a dating relationship.